2017
DOI: 10.1371/journal.pone.0173599
|View full text |Cite
|
Sign up to set email alerts
|

Aridity influences the recovery of vegetation and shrubland birds after wildfire

Abstract: Wildfires play a determining role in the composition and structure of many plant and animal communities. On the other hand, climate change is considered to be a major driver of current and future fire regime changes. Despite increases in drought in many areas of the world, the effects of aridity on post-fire colonization by animals have been rarely addressed. This study aims to analyse how a regional aridity gradient affects post-fire recovery of vegetation, bird species richness and the numbers of four early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
(70 reference statements)
0
15
0
1
Order By: Relevance
“…Elevation and gypsum content did not change across a broad geographic gradient, as changes in other environmental variables often do (e.g., mean annual rainfall; Barry and Elith , Puig‐Gironès et al. , Kenny et al. ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Elevation and gypsum content did not change across a broad geographic gradient, as changes in other environmental variables often do (e.g., mean annual rainfall; Barry and Elith , Puig‐Gironès et al. , Kenny et al. ).…”
Section: Discussionmentioning
confidence: 91%
“…Elevation and gypsum content did not change across a broad geographic gradient, as changes in other environmental variables often do (e.g., mean annual rainfall; Barry and Elith 2006, Puig-Giron es et al 2017, Kenny et al 2018). Furthermore, variability in the Mallee Emu-wren fire response was not associated with differences in vegetation type, as other authors have found (Gosper et al 2012, 2013, Janion-Scheepers et al 2016.…”
Section: Important Environmental Covariates: Elevation and Gypsum Conmentioning
confidence: 85%
See 1 more Smart Citation
“…Puig-Gironès et al (2017) reported rainfall effects on the post-fire recovery patterns of plant and bird populations in a Mediterranean region. the effective number of plant species visited by ant species or specialization at the ant level).…”
Section: Discussionmentioning
confidence: 99%
“…In these areas, it is essential to understand how CAD may harm ecosystem stability, and consequently, compromise the future use of these ecosystem resources by humans. Moreover, aridity may interact with disturbance to intensify ecosystem instability (Pulla et al 2015, Puig-Gironès et al 2017. Consequently, ecosystem stability would be lower in more disturbed areas than in relatively undisturbed areas.…”
Section: Introductionmentioning
confidence: 99%